2007
DOI: 10.1109/acc.2007.4282533
|View full text |Cite
|
Sign up to set email alerts
|

Active damping of automotive powertrain oscillations by a partial torque compensator

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In recent years, the greater demand for passenger comfort, which requires a reduction of the noise and vibration characteristics of vehicles, has led to the design of proper models for conventional vehicle drivetrains and to the development of different control strategies to minimize the effects of drivetrain oscillations: robust pole placement (Stewart et al, 2005), H ∞ optimization (Lefebvre et al, 2003), linear quadratic gaussian control design with loop transfer recovery (LQG/LTR) (Berriri et al, 2008) and even model predictive control (MPC) (Rostalski et al, 2007). Although the majority of the control strategies that are implemented on real vehicles are based on heuristics and look-up tables, it was shown that MPC has a large potential for control of automotive subsystems, e.g., mechatronic actuators (Di Cairano et al, 2007), driveline (Saerens et al, 2008), engine (Di Cairano et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the greater demand for passenger comfort, which requires a reduction of the noise and vibration characteristics of vehicles, has led to the design of proper models for conventional vehicle drivetrains and to the development of different control strategies to minimize the effects of drivetrain oscillations: robust pole placement (Stewart et al, 2005), H ∞ optimization (Lefebvre et al, 2003), linear quadratic gaussian control design with loop transfer recovery (LQG/LTR) (Berriri et al, 2008) and even model predictive control (MPC) (Rostalski et al, 2007). Although the majority of the control strategies that are implemented on real vehicles are based on heuristics and look-up tables, it was shown that MPC has a large potential for control of automotive subsystems, e.g., mechatronic actuators (Di Cairano et al, 2007), driveline (Saerens et al, 2008), engine (Di Cairano et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Berriri et al developed a partial torque compensator in order to actively dampen powertrain oscillations. 12 In similarity with the previous studies, the developed controller uses engine speed measurement as an input to the controller to calculate the corrective torque that will oppose the shuffle phenomenon. The difference of the proposed methodology from previous studies is that the control synthesis is more or less independent of the driveline characteristics and non linearities, as it is employing a simplified model of the engine without the precise characteristics of the driveline.…”
Section: Introductionmentioning
confidence: 96%
“…In addition to the backlash problem, the limitations in the control period of actuators used for active damping of automotive drivetrains present additional problems. An example of such an actuator is the engine, 16 in which the generated torque corresponds to the control input. An engine cannot update the control input at the timing synchronized with that of a digital controller.…”
Section: Introductionmentioning
confidence: 99%
“…17 Modeling of an engine with a fixed maximal delay and the H ∞ controller design in continuous-time domain ensured the phase margin to cope with the mechanism to update engine torque. 18 In addition, predictive controllers have been proposed to compensate for the engine delay, 16,19,20 and their effectiveness has been experimentally validated.…”
Section: Introductionmentioning
confidence: 99%